2006
DOI: 10.1016/s0968-8080(06)28265-x
|View full text |Cite
|
Sign up to set email alerts
|

Romance and Sex: Pre-Marital Partnership Formation among Young Women and Men, Pune District, India

Abstract: Using qualitative and survey data in a rural and an urban slum setting in Pune district, India, this paper describes patterns of pre-marital romantic partnerships among young people aged 15-24, in spite of norms that discourage opposite-sex interaction before marriage. 25-40% of young men and 14-17% of young women reported opposite-sex friends. Most young people devised strategies to interact with others, largely from the same neighbourhood. There were wide gender differences with regard to making or receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 5 publications
4
46
0
Order By: Relevance
“…1,[3][4][5][6][7] However, our results corroborate findings of previous studies 1, 3,6 in that young women were less likely than young men to report condom use within premarital relationships. Our multivariate analyses revealed three major correlates of premarital condom use among young women and men.…”
Section: Condom Use Before Marriage and Its Correlates In Indiasupporting
confidence: 88%
See 1 more Smart Citation
“…1,[3][4][5][6][7] However, our results corroborate findings of previous studies 1, 3,6 in that young women were less likely than young men to report condom use within premarital relationships. Our multivariate analyses revealed three major correlates of premarital condom use among young women and men.…”
Section: Condom Use Before Marriage and Its Correlates In Indiasupporting
confidence: 88%
“…2 Several small-and large-scale studies that explored the premarital sexual behavior of Indian youth have also found that condom use is limited. [3][4][5][6][7][8] Studies exploring correlates of condom use in India have generally focused on married men and women of reproductive age, or on such vulnerable groups as female sex workers, clients of sex workers, people living with HIV, migrants and men who have sex with men. [9][10][11][12][13][14][15][16][17][18] Few studies have examined factors associated with young people's use of condoms, particularly in premarital relationships.…”
mentioning
confidence: 99%
“…24,25 The presurvey qualitative phase-conducted in 2003-comprised 13 focus group discussions with youth; 21 interviews with local health care providers, teachers and other individuals familiar with youth; and 13 in-depth interviews with selected youth. This phase was intended to inform the development of the survey instrument and gain insight into the romantic and sexual experiences of youth.…”
Section: Methodsmentioning
confidence: 99%
“…Though there have been very few studies of premarital sexual activity in India, a recent survey in Pune District found that 10% of young women were sexually active before marriage. 15 A relatively small share of young Indian women may be exposed to pregnancy risk, but for those who are sexually active, condom use is quite rare-a recent study found that only 7% of sexually active young women reported that they had ever used a condom. 16 Because of the stigma associated with premarital sexual activity, offering pericoital contraception via pharmacies may provide a reasonable alternative for young women who find clinic-based family planning services unreceptive and do not feel comfortable purchasing condoms or insisting on condom use by their partners.…”
Section: Lack Of Dual Protectionmentioning
confidence: 99%